2016
DOI: 10.3390/rs8040353
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Plastic-Mulched Farmland by Landsat-8 OLI Imagery Using Spectral and Textural Features

Abstract: Abstract:In recent decades, plastic-mulched farmland has expanded rapidly in China as well as in the rest of the world because it results in marked increases of crop production. However, plastic-mulched farmland significantly influences the environment and has so far been inadequately investigated. Accurately monitoring and mapping plastic-mulched farmland is crucial for agricultural production, environmental protection, resource management, and so on. Monitoring plastic-mulched farmland using moderate-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The following improvements could be considered in the future. If only single-phase UAV RGB images can be acquired, we could try to transform the DN value to different indices, or we could extract the different texture information of the image to enhance the difference between the tobacco films and the roads/buildings [29]. We also could try to use an object-oriented classification method to first extract building objects [30,31], remove the buildings from the UAV RGB images, and then use our proposed method to extract the tobacco fields.…”
Section: Discussionmentioning
confidence: 99%
“…The following improvements could be considered in the future. If only single-phase UAV RGB images can be acquired, we could try to transform the DN value to different indices, or we could extract the different texture information of the image to enhance the difference between the tobacco films and the roads/buildings [29]. We also could try to use an object-oriented classification method to first extract building objects [30,31], remove the buildings from the UAV RGB images, and then use our proposed method to extract the tobacco fields.…”
Section: Discussionmentioning
confidence: 99%
“…This study found out that 902-hectare area is suitable to be used for upcoming agriculture area in Gokceada. Landsat 8 has also been used by Hasituya et al to monitor plasticmulched farmland [4]. Plastic mulch is widely used all over the world, especially in China to suppress weeds and conserve water in crops, fruits and vegetables production.…”
Section: Agriculture and Forestrymentioning
confidence: 99%
“…Plastic-mulched farmland is identified as it has the same spectrum curve shape as soil but with a higher reflectance than other classes on SWIR bands. A new scheme is proposed in [4] which integrates spectral and textual features that is able to monitor the plastic-mulched farmland and at the same time evaluating the performance of Support Vector Machine algorithm using OLI, Google Earth imagery and ancillary data.…”
Section: Agriculture and Forestrymentioning
confidence: 99%
“…SVMs are a supervised non-parametric statistical learning technique that makes no assumptions on the underlying data distribution [53]. We decided to use SVMs for this classification because compared to more traditional classification approaches (e.g., Maximum Likelihood Classifier), SVMs were found to perform better for a variety of classifications in different contexts (e.g., different classification scopes, classification schemes, and classification features) [53][54][55][56][57][58][59][60][61]. In general, SVMs are binary classifiers that delineate two classes by fitting an optimal separating hyperplane to the training data in multidimensional feature space [52].…”
Section: Support Vector Machines For Change Detectionmentioning
confidence: 99%